BS EN IEC 61753-022-07. Fibre optic interconnecting devices and passive components. Performance standard. Part 022-07. Hardened fibre optic connectors terminated on multimode fibre for category A. Outdoor aerial environment (12th March 2021) - British Standards Institution,
No abstract available